Legacies of Institutionalized Redlining: A Comparison Between Speculative and Implemented Mortgage Risk Maps in Chicago, Illinois. Issue 2 (4th March 2022) - Xu, Wenfei
ABSTRACT: How did institutionalized discriminatory lending policies implemented under the guidance of the Federal Housing Administration (FHA)'s mortgage risk maps impact neighborhood trajectories? Have these spatially restrictive credit designations influenced home value, homeownership, and racial segregation? Using the FHA mortgage risk map of Chicago, Illinois, for new loan guarantees as a case study, I measure outcomes between credit zones and compare these risk regions with the Home Owners' Loan Corporation (HOLC) Residential Security Maps, which represent post hoc measures of mortgage risk and were likely not directly used in loan activities. For areas excluded from FHA loan guarantees, the results suggest a negative impact on home values and homeownership rates and weakly decreased segregation between 1940 and 1980. They also suggest an overcorrection of home values, an undercorrection of homeownership, and an increase in racial segregation in excluded neighborhoods between 1980 and 2010 when these areas may have experienced capital reinvestment. In comparison with the HOLC map, the effects on tracts in Chicago rated worst by the FHA are clearer and suggest a more significant impact during the period of discriminatory mortgage lending.